Visual Identity Pondok Roti Da Jon (International Forum of Researchers and Lecturers, 2025)
Pondok Roti Da Jon is a small bakery business that has been established since 1986 in Bukittinggi. Pondok Roti Da Jon produces various traditional breads such as Malabar bread and fried bread. The Malabar bread produced by Pondok Roti Da Jon consists of two variants, namely original and pandan, while the fried bread consists of variants filled with coconut and banana. In the production process, Pondok Roti Da Jon is still done manually using improvised tools. Pondok Roti Da Jon's consumers are middle class and come from all walks of life, from children, teenagers, and adults. Currently, Pondok Roti Da Jon products are developing in a small-scale industry that grows by word of mouth, and its sales are distributed to markets around Bukittinggi. This design uses the 4D method consisting of 4 stages, namely the definition, design, development, and dissemination stages. Data collection techniques are primary data based on observations, interviews, and documents and secondary data obtained from books, journals, documents, newspapers, and the internet. The data analysis method is based on SWOT analysis, namely, Strengths, Weaknesses, Opportunities, and Threats. The concept used by Pondok Roti Da Jon is